2015
DOI: 10.1055/s-0034-1396333
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Hypertension: Clinical Manifestations of 7 Cases

Abstract: The association of multiple lesions strongly suggests malignant hypertension. However even in cases with only one lesion malignant hypertension should be kept in mind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Malignant hypertension is a hypertensive urgency characterized by grade III/IV retinopathy and widespread endothelial damage [13]. Steinegger et al [14] investigated the types of symptoms and ocular lesions observed with ocular fundus examination, ocular fundus photography, fluorescein angiography and optical coherence tomography in a small case series of 7 patients with malignant hypertension.thay found that the Median systolic blood pressure (BP) was 205 mmHg±21.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant hypertension is a hypertensive urgency characterized by grade III/IV retinopathy and widespread endothelial damage [13]. Steinegger et al [14] investigated the types of symptoms and ocular lesions observed with ocular fundus examination, ocular fundus photography, fluorescein angiography and optical coherence tomography in a small case series of 7 patients with malignant hypertension.thay found that the Median systolic blood pressure (BP) was 205 mmHg±21.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, retinal fundoscopy should be performed in all patients presenting with severely increased blood pressure on examination [2]. It is due to the fact that typical retinal changes are dynamic, start to regress immediately upon the implementation of the antihypertensive treatment and do not persist for longer than 2-3 months [2,15]. Although in some cases, when patients present with extreme signs of blood pressure elevation, such as hypertensive encephalopathy and MHT is suspected, Grade 3-4 ocular changes might be absent during their initial examination [16].…”
Section: Diagnostic Difficultiesmentioning
confidence: 99%
“…Tryfon и соавт. [27] отмечают, что она представляет собой опасное для жизни состояние, вызванное резким повышением системного артериального давления. Острая гипертония может вызывать ряд изменений на глазном дне [22], включая ретинопатию, хориопатию и нейропатию, что приводит к серьезному ухудшению зрения.…”
Section: гипертоническая ретинопатия при злокачественной артериальнойunclassified